Effects of Applying Foot Massage and Lemongrass Oil Aromatherapy on Sleep Quality of Menopausal Women: Pemberian Massage Kaki dan Aromaterapi Minyak Sereh (Lemongrass) Terhadap Kualitas Tidur pada Ibu Menopause - Sifah, Lutfi As; Rahmadhani, Wulan; Sumarni, S (Prosiding University Research Colloquium, 2023)
Sleep quality highly influences the health of menopausal women. Sleep is a vital physiological phenomenon. Non-pharmacological can be an alternative to reduce poor sleep quality in menopausal women by applying foot massage and lemongrass oil aromatherapy. To identify the effect of applying foot massage and lemongrass oil aromatherapy on sleep quality in menopausal women. This study is a case study. Data were obtained from interviews, observations, and literature studies. The instruments used were informed consent, Pittsburgh Sleep Quality Index (PSQI) questionnaires to assess sleep quality with a score of ? 5 for good quality and ? 5 for poor quality of sleep, and lemongrass oil aromatherapy. This study involved 5 menopausal women aged 45-55 years. The therapy was conducted for 7 consecutive days. Before the treatment, all respondents (100%) had poor sleep quality but after applying foot massage and lemongrass oil aromatherapy, they had good sleep quality indicated by a decrease in the PSQI score. Applying foot massage and lemongrass oil aromatherapy is effective in improving sleep quality in menopausal women aged 45-55 years.